Conditions for effective macroprudential policy interventions - Fahad Khan; Arief Ramayandi; Marcel Schröder (Asian Development Bank (ADB), 2020)
This paper aims at identifying effective macroprudential policy (MPP) interventions and analysing the macroeconomic conditions that promote them. We define effective MPP interventions as those that stabilize its underlying target variable, such as credit growth, house price growth, etc. For our analysis, we construct a new database that documents the use of a large number of MPP instruments for 61 advanced and emerging market economies from 2000 to 2016. The new feature of the database is that it maps every recorded MPP intervention in these economies and over this period to stabilize a specific target variable category for banking, health, domestic loans, the exchange rate, foreign capital movements, and house prices. Using this dataset, we introduce a practical way for defining the macroprudential policy effectiveness. We find that MPP interventions are more likely to be effective when several prudential measures are taken together, but at the same time avoid the diminishing returns of repeated MPP tightening. Monetary tightening seems to override the effectiveness of MPP instruments. The output gap, credit cycle, external debt, current account, and global risk appetite also count for the likelihood of MPP successes. The paper provides a guideline for the effective conduct of MPPs.
Keywords: E32; E58; G15; G28; 330; effectiveness; financial stability; macroprudential policy; probabilistic analysis